Short-term effects of analysts recommendations in Spanish blue chips returns and trading volumes - Josep García Blandón; Josep Maria Argilés Bosch (Estudios de Economía, 2009)
The purpose of this paper is to investigate the effects of stock recommendations in returns and trading volumes. Unlike previous research we have investigated the five most usual types of recommendations: buy, outperform, hold, underperform and sell. The methodology we propose is also different from previous studies. From our results we conclude that positive (negative) abnormal returns are associated to positive (negative and neutral) recommendations, the day of publication of the recommendation and the day before, but not the day after publication. We also document an asymmetry in the effect of recommendation on the stock trading volume, following the sign of the recommendation.
Keywords: G14; 330; stock recommendations; abnormal returns; trading volumes; price pressure hypothesis; information content hypothesis